Molecular Structure and Vibrational Analysis of 2-(4-methoxyphenyl)-2, 3-Dihydro-1H-Perimidine using Density Functional Theory - A.Nathiya; H.Saleem; T.Jayakumar; A.Rajavel; N.Ramesh Babu (Journal of New Developments in Chemistry, 2017)
The compound 2-(4-methoxyphenyl)-2, 3-dihydro-1H-perimidine (MPDP) was synthesized. The molecular structure and its functional groups were characterized with the help of Fourier Transform Infrared: FTIR/ Fourier Transform FT-Raman spectra in the regions of 400-4000/50-4000cm-1, respectively. The geometrical parameters, harmonic vibrational wavenumbers, Infrared (IR) & Raman scattering intensities, Nuclear Magnetic Resonance (NMR) chemical shift and Ultraviolet-Visible (UV-Vis) spectra were computed using B3LYP/6-311++G(d,p) level of theory. The complete vibrational analysis were made on the basis of Potential energy distribution (PED) calculation with the help of VEDA4 programme. The Highest occupied molecular orbital (HOMO) – Lowest unoccupied molecular orbital (LUMO) energy gap and intra-molecular charge transfer (ICT) were studied using NBO analysis. The first order hyperpolarizability (β0) and other related properties (β, α0, Δα) of MPDP were computed. The molecular electrostatic potential (MEP), Mulliken atomic charges were calculated using the same level of theory. In addition, the various thermodynamic parameters were also calculated.
Keywords: FT-IR